Efficacy and residual effect of Mosqinok (Novaluron 0.8 P) against Culex quinquefasciatus larvae for the control of lymphatic filariasis in semi-field conditions in Bangladesh (Bangladesh Journal of Zoology, 2026)
Insect Growth Regulators (IGRs) or Chitin Synthesis Inhibitors (CSIs) are supposed to inhibit the formation of chitin microfibrils in newly synthesized cuticle during molting by the retardation of larval growth and developmental processes during their life cycle. There are relatively few data on the morphological effects of CSI or IGR on mosquitoes in Bangladesh. In this study, the impact of Mosqinok (0.8P Novaluron) on mortality and pupation of Cx. quinquefasciatus was evaluated. Toxicity bioassays showed that Novaluron is toxic to 4th instar larva when exposed in 50L plastic drums at a dose rate of 1/4th of 1 tablet (10g) in 25L water. The larvae that were treated with Novaluron exhibited reduced activity levels and started to die after 24h of exposure, with a mortality rate of 6.67%, which reached 100% within 10 days. Novaluron-treated larvae exhibited toxic effects that inhibited molting, resulting in the failure of pupation. One-way ANOVA analysis revealed significant differences in larval mortality (p < 0.05) and pupal emergence (p < 0.01) between the treatment and control groups. This product also exhibited residual activity for up to 91 days after a single application. To conclude, the IGR larvicide has the potential to significantly contribute to vector control programs, particularly in terms of its efficacy and strategies for managing insecticide resistance in vector mosquitoes. It is recommended that additional field studies be conducted on the effectiveness of Novaluron against various mosquito species in diverse habitats throughout BangladeshBangladesh J. Zool. 53(3): 357-372, 2025